Gastrointestinal hyperplasia with altered expression of DNA polymerase beta. - Katsuhiko Yoshizawa (Public Library of Science (PLoS), 2009)
Background Altered expression of DNA polymerase beta (Pol beta) has been documented in a large percentage of human tumors. However, tumor prevalence or predisposition resulting from Pol beta over-expression has not yet been evaluated in a mouse model. Methodology/principal findings We have recently developed a novel transgenic mouse model that over-expresses Pol beta. These mice present with an elevated incidence of spontaneous histologic lesions, including cataracts, hyperplasia of Brunner's gland and mucosal hyperplasia in the duodenum. In addition, osteogenic tumors in mice tails, such as osteoma and osteosarcoma were detected. This is the first report of elevated tumor incidence in a mouse model of Pol beta over-expression. These findings prompted an evaluation of human gastrointestinal tumors with regard to Pol beta expression. We observed elevated expression of Pol beta in stomach adenomas and thyroid follicular carcinomas, but reduced Pol beta expression in esophageal adenocarcinomas and squamous carcinomas. Conclusions/significance These data support the hypothesis that balanced and proficient base excision repair protein expression and base excision repair capacity is required for genome stability and protection from hyperplasia and tumor formation.